Dangerous drugs an easy-to-use refernce for parents and professionals - Falkowski, Carol L. (A Hazelden guidebook., 2000)
A non-sensationalist reference providing information on drug use, medical consequences, psychological and behavioural effects, names and forms, symptoms, signs of abuse and more. The book's scope covers illegal and legal drugs, prescription and over-the-counter drugs and herbal remedies.